Isomorphisms on Strong Fuzzy Graphs - Trisanti, Yuliana; Saleh, Hairus (SAINTIS Publishing, 2024)
Fuzzy graph is a graph consisting of pairs of vertices and edges that have a membership degree that contains a closed interval of real numbers on each edge and vertex. A fuzzy graph is said to be a strong fuzzy graph if the membership degree of edge with the minimum membership degree of vertex and the same membership degree of vertex for each edge with . This paper explains the properties of fuzzy graph isomorphism including weak isomorphism, co-weak isomorphism, and isomorphism in strong fuzzy graphs.